PENGARUH PEMBANGUNAN EMBUNG (PENAMPUNGAN AIR) TERHADAP HASIL PANEN PETANI DI DESA PACCEKKE KECAMATAN SOPPENG RIAJA KABUPATEN BARRU - Yusuf Asri; Dalilul Falihin (Universitas Negeri Makassar, 2022)
Moh. Yusuf Asri, 2022. The Effect of Embung (Water Storage) Development on Farmers' Harvests in Pacekke Village, Soppeng Riaja District, Barru Regency. Thesis, Faculty of Social Sciences and Law, Makassar State University. Supervised by Dalilul Falihin and Syarifah Balkis. The research was carried out with the following objectives: 1) To find out the description of the construction of a reservoir (water reservoir) in Pacekke Village, Soppeng Riaja District, Barru Regency. 2) To find out the description of farmers' harvests in Pacekke Village, Soppeng Riaja District, Barru Regency and 3) To find out whether there is any effect of the construction of a reservoir (water reservoir) on farmers' harvests in Pacekke Village, Soppeng Riaja District, Barru Regency. The type of research used is descriptive quantitative. The variables of this study consisted of the construction of reservoirs (water reservoirs) (variable X) and the yield of petahi (variable Y) data collection techniques using observation, questionnaires/questionnaires and documentation. The data analysis technique used is descriptive statistics and inferential analysis. Based on the research, it is known that: 1) The construction of a reservoir (water reservoir) in Pacekke Village, Soppeng Riaja District, Barru Regency is included in the